2010
DOI: 10.1007/s10295-010-0794-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trace metals on ethanol production from synthesis gas by the ethanologenic acetogen, Clostridium ragsdalei

Abstract: The effect of trace metal ions (Co²+, Cu²+, Fe²+, Mn²+, Mo⁶+, Ni²+, Zn²+, SeO₄⁻ and WO₄⁻) on growth and ethanol production by an ethanologenic acetogen, Clostridium ragsdalei was investigated in CO:CO₂-grown cells. A standard acetogen medium (ATCC medium no. 1754) was manipulated by varying the concentrations of trace metals in the media. Increasing the individual concentrations of Ni²+, Zn²+, SeO₄⁻ and WO₄⁻ from 0.84, 6.96, 1.06, and 0.68 μM in the standard trace metals solution to 8.4, 34.8, 5.3, and 6.8 μM,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
78
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 31 publications
6
78
1
Order By: Relevance
“…"C. ragsdalei" or strain "P11" was isolated from duck pond sediment by researchers from The University of Oklahoma and Oklahoma State University and is described in a patent [154]. "C. ragsdalei" has been explored for the production of ethanol from syngas [155][156][157], with growth temperatures of 32 °C-37 °C [157] and a batch fermentation reported ethanol concentration of 1.99 g L −1 [158]. In a 100 L stirred tank reactor (STR) an ethanol concentration of 25.26 g L −1 was achieved over a fermentation duration of 59 days [159].…”
Section: Ethanol Productionmentioning
confidence: 99%
“…"C. ragsdalei" or strain "P11" was isolated from duck pond sediment by researchers from The University of Oklahoma and Oklahoma State University and is described in a patent [154]. "C. ragsdalei" has been explored for the production of ethanol from syngas [155][156][157], with growth temperatures of 32 °C-37 °C [157] and a batch fermentation reported ethanol concentration of 1.99 g L −1 [158]. In a 100 L stirred tank reactor (STR) an ethanol concentration of 25.26 g L −1 was achieved over a fermentation duration of 59 days [159].…”
Section: Ethanol Productionmentioning
confidence: 99%
“…However, the addition of Mn 2+ has no significant effect on sugar yield, and the saccharification yields for the samples with Mn 2+ are the same or similar to those of the saccharification samples without added metal ions (Ramachandran et al 2015). Ethanol production does not change considerably at higher concentrations of Mn 2+ (Saxena and Tanner 2011). However, trace manganese enhances butyric acid production (Liu et al 2015).…”
Section: Introductionmentioning
confidence: 83%
“…Mn 2+ is an essential trace element for microbial growth that improves the activity of cellulase and yeast (Saxena and Tanner 2011;Lakkana et al 2012). The increase in activity and cellulose content is favorable for fermentation (Li et al 2013;Deesuth et al 2015).…”
Section: Process Optimization Of Ethanol Production From Cornstalksmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies with C. ljungdahlii showed that reducing or completely removing YE from fermentation medium increased ethanol concentration from 1 g/L to 48 g/L (Phillips et al, 1993;Vega et al, 1989). The increase in the concentrations of Ni 2+ , Zn 2+ , SeO4 -and WO4 -from 0.84 µM, 6.96 µM, 1.06 µM and 0.68 µM to 8.4 µM, 34.8 µM, 5.3 µM and 6.8 µM, respectively, improved ethanol production by C. ragsdalei by fourfold (Saxena and Tanner, 2011).…”
Section: Medium Componentsmentioning
confidence: 93%